PEWARISAN SEJARAH PEWARISAN SEJARAH MELALUI ADAT SAURMATUA DI DOLOKSANGGUL, KABUPATEN HUMBANG HASUNDUTAN, PROVINSI SUMATERA UTARA - indah manulang, indah sari manulang (SEUNEUBOK LADA: Jurnal ilmu-ilmu Sejarah, Sosial, Budaya dan Kependidikan, 2022)
Culture is one of the habits carried out by a group of people that contains a system of ideas, actions, and is the result of human work which is one of the important basics in human life and is carried out from generation to generation and is owned by every community group, especially the Toba Batak community. The purpose of this study was to find out how the history of the Saurmatua custom in the Toba Batak community in Doloksanggul, to find out the implementation of the Saurmatua custom in the Toba Batak community in Doloksanggul and to find out what values ​​were inherited in the Saurmatua ceremony of the Toba Batak community in Doloksanggul. The research method that the author uses in completing this thesis is a descriptive qualitative method with an anthropological approach through the ethnographic method. The results of this study are the history of the Saurmatua custom that occurred because it was inherited by the ancestors of the Toba Batak people, because they wanted to make the last respect for their parents, and because they carried out the fifth commandment in Protestant Christianity. The stages in the implementation of the Saurmatua custom begin at the initial stage consisting of pasada dung, paoptree/mompo events, martonggo raja and corpse manortori events. The implementation stage (big party event), which consists of the manambol stage, the stage of condolences from the family, the stage of the manortor event in Alaman, the manaruhon tu udean event, the meal together, the jambar distribution event until the completion of the Saurmatua traditional event. And there are also values ​​inherited in the implementation of the Saurmatua custom which contains four important values ​​such as religious values, social values, moral values ​​and customary values.